2006
DOI: 10.1172/jci27180
|View full text |Cite
|
Sign up to set email alerts
|

Activated macrophages are essential in a murine model for T cell-mediated chronic psoriasiform skin inflammation

Abstract: The CD18 hypomorphic (CD18 hypo ) PL/J mouse model clinically resembling human psoriasis is characterized by reduced expression of the common chain of b 2 integrins (CD11/CD18) to only 2-16% of WT levels. Previously we found that this chronic psoriasiform skin inflammation also depends on the presence of CD4 + T cells. Herein we investigated the role of macrophages in this CD18 hypo mouse model. Activated macrophages were significantly increased in lesional skin as well as in inflamed skin draining lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
225
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(244 citation statements)
references
References 64 publications
17
225
2
Order By: Relevance
“…Psoriatic lesions contain mast cells (39), and complement activation is suggested to be important in disease mediation in mouse arthritis and patients with Ps (40,41), whereas the contributions of mast cells, FcγRIII, and C5 in this disease model seem to be redundant. Conversely, increased frequency of monocytes/macrophages, depletion experiments, and the suppressor function of macrophage-derived ROS clearly argue in favor of a role of monocytes/macrophages in the disease, which is in accordance with the findings in patients with the psoriatic form of skin lesions (42,43) and arthritis (22).…”
Section: Discussionsupporting
confidence: 86%
“…Psoriatic lesions contain mast cells (39), and complement activation is suggested to be important in disease mediation in mouse arthritis and patients with Ps (40,41), whereas the contributions of mast cells, FcγRIII, and C5 in this disease model seem to be redundant. Conversely, increased frequency of monocytes/macrophages, depletion experiments, and the suppressor function of macrophage-derived ROS clearly argue in favor of a role of monocytes/macrophages in the disease, which is in accordance with the findings in patients with the psoriatic form of skin lesions (42,43) and arthritis (22).…”
Section: Discussionsupporting
confidence: 86%
“…3 Embryonic macrophages appear to play a positive trophic role that may have parallel reparative functions in many adult tissues undergoing repair and cellular replacement. 1,20 A number of studies have suggested that infiltrating macrophages along with the trophic factors they release participate in tissue repair of the kidney, 20 -22 brain, 23 skin, 24,25 lung, 26 liver, 27 heart, 28 gastrointestinal tract, 29,30 and skeletal muscle. 31,32 Indeed, the pleiotrophic roles for CSF-1 in reproduction, development of multiple organ systems, and maternal-fetal interactions during pregnancy by macrophage-mediated processes have also been well defined.…”
mentioning
confidence: 99%
“…However, macrophage-derived proinflammatory mediators such as TNF-␣ may play a crucial role in human psoriasis (3) and in mouse models of psoriasis (4 -6). Accordingly, selective depletion of macrophages by liposome-encapsulated clodronate in mouse models and treatment of the patients with the TNF-␣ antagonist etanercept resulted in improvement of skin inflammation in murine models and human psoriasis (4,5,7). Apart from TNF-␣, a considerable number of cytokines, including the NF-B-induced IL-12, IL-15, IL-20, and IL-23 as well as IFN-␣ and IFN-␤, have been shown to participate in the pathogenesis of psoriasis (8,9).…”
mentioning
confidence: 99%
“…The active form of NF-B is a dimer formed by members of the NF-B/Rel family of proteins, with the p50/p65 dimer being the most abundant. Phosphorylation of the inhibitor IB by the IB kinase (IKK) 4 complex is a central step in NF-B activation, leading to IB degradation and subsequent nuclear translocation of p50/p65 and other NF-B subunits (10,13). The transcriptional activity of the p50/p65 dimer is further enhanced by the IKKdependent phosphorylation of p65 on Ser 536 (13,14).…”
mentioning
confidence: 99%